Analysis of School Management Success Factors in the Teaching Activity Process - Nisak, Hernik Khoirun (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
The effective school assessment model is one of the instruments that education managers hope to use to determine the level of success of each school. The results of this assessment can then be used as consideration for making efforts to improve the school. A school that has a good, transparent and accountable management system, and is able to empower every important component of the school, both internally and externally, in order to achieve the school's vision, mission, and goals effectively and efficiently. The concept of an effective school is a school that is able to optimize all input and processes for achieving educational output, namely school achievement, especially student achievement which is characterized by the possession of all abilities in the form of competencies required for learning. The characteristics of effective schools are: 1) strong principal leadership. 2) high expectations for student achievement, 3) emphasis on basic skills, and 4) order and a controlled atmosphere. Effective school leadership by the principal because the principal is a figure (key person) in realizing the vision, mission and goals of the school, namely an effective and efficient school